Cystic Lymphangioma of the Pancreas: About A Case and Literature Review - Kouame, Dr Kouassi Armel Serge; El Mehdi, Dr Aboulfeth; Mohamed, Dr Bouzroud; Mohamed, Pr Najih; Hakim, Pr Kaoui; Ahmed, Pr Bounaim (International Journal of Innovative Research in Medical Science, 2021)
Cystic lymphangioma is a rare malformative benign tumour of the lymph vessels, its histogenesis is still hypothetical. This tumour is mainly found in child’s neck and axillary, the pancreatic location remains exceptional and represents less than 1% of whole lymphangiomas, and occurs more frequently in women and especially in the left pancreas. Its clinical presentation is polymorphic; however, the diagnosis can’t be specifically evoked by imaging and requires therefore histological confirmation. Surgery remains the only curative treatment. We report in this work the case of an incidentally discovered cystic lymphangioma of the pancreatic tail in a 58-year-old woman. The histological study of the surgical specimen concluded on a benign cystic lymphangioma. On later surgical outcomes, the patient developed a pseudokyst of the remaining pancreas and today she has not had any recurrences. The aim of this article is to share our experience in the management of this case and to review the clinical and therapeutic aspects of this rare pathology.